Pengaruh Profitabilitas, Growth Opportunity Dan Struktur Modal Terhadap Nilai Perusahaan Pada PT Graha Layar Prima TBK Periode 2014-2024 - Anisa Aulia; Jeni Irnawati (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
This study is motivated by fluctuations in the financial performance of PT Graha Layar Prima Tbk during the period 2014–2024, which have the potential to significantly affect the firm value. This condition reflects the importance of conducting an in-depth analysis of the factors influencing firm value in order to identify the most dominant variables. The purpose of this study is to examine the effect of profitability, growth opportunity, and capital structure on firm value at PT Graha Layar Prima Tbk for the period 2014–2024.n This study employs a quantitative approach with a descriptive method to provide a clear overview of the relationships among the variables. The data used are secondary data in the form of the company’s annual financial statements over an 11-year period. The data analysis techniques include descriptive analysis, classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation), multiple linear regression analysis, coefficient of determination test, and hypothesis testing consisting of partial tests (t-test) and simultaneous tests (F-test). The results show that partially, profitability and growth opportunity do not have a significant effect on firm value, while capital structure has a significant effect on firm value. Simultaneously, profitability, growth opportunity, and capital structure have a significant effect on firm value. The conclusion of this study indicates that capital structure is the most dominant factor influencing firm value during the research period. The findings are expected to serve as a consideration for company management in determining funding policies to enhance firm value.